Influence of the ‘News Finds Me’ Perception on News Sharing and News Consumption on Social Media - Segado-Boj, Francisco; Díaz-Campo, Jesús; Quevedo Redondo, Raquel (Communication Today, 2025)
The study focuses on ‘News Finds Me’ perception, i.e. the belief that users can stay informed enough without actively following traditional news media while relying on social media and personal contacts. The text analyses the influence between this perception and news consumption (“news internalising”) and sharing (“news externalising”). Uses & Gratifications sought (“information seeking”, “social interaction” and “impression management”) were considered as moderating variables. Survey based results (n = 96) show that ‘News Finds Me’ perception is positively correlated with news internalising but not with news externalising. It is thus concluded that the mere presence of the ‘News Finds Me’ perception does not encourage news sharing attitudes. The study also brings evidence to support a relationship between news internalising and news externalising habits, which influence each other mutually and can moderate other factors in news consumption and dissemination on social media. It is concluded that the presence of the ‘News Finds Me’ perception does not encourage news sharing attitudes.